Early Chondrogenic Differentiation of Spheroids for Cartilage Regeneration: Investigation of the Structural and Biological Role of a Lactose-Modified Chitosan - Marco Conz; Francesca Scognamiglio; Ivan Donati; Susi Zara; Gabriella Teti; Maurizio Romano; Eleonora Marsich (Polysaccharides, 2025)
Long-term solutions for cartilage repair after injury are currently being investigated, with most research aiming to exploit the regenerative and chondrogenic differentiation potential of stem-cell-based spheroids. The incorporation of the bioactive polymer CTL, a lactose-modified chitosan, into spheroids is a strategy to improve cell viability and accelerate type II collagen gene expression. In this work, the role of CTL in influencing the dynamics of spheroid formation and its interplay with cell membrane adhesion molecules (integrins and cadherins) and cytoskeletal components is elucidated. The results indicate that CTL is actively involved in the reorganization of cells into spheroids. An analysis of the effects of physical form of CTL (rehydrated polymer coating or polymer solution) in stimulating peculiar biological responses indicates that CTL matrix in spheroids facilitates an early phase of chondrogenic differentiation. Once the CTL matrix is included in spheroids, there is an increase in COL2A1 gene expression and matrix deposition, regardless of the initial physical form of CTL. Overall, these results contribute to a better understanding of the dynamics of spheroid formation in the presence of the polymer and on its bioactive role in mesenchymal stem cell spheroids.